Optimizing Oral Drop Formulations of Sand Sea Cucumber (Holothuria Scabra) and Red Dragon Fruit Peel (Hylocereus Polyrhizus) for Improved Postoperative Healing in Tongue Cancer Patients (Preliminary Study) - Essie Octiara; Azrul Hafiz Abdul Aziz; Farid Bin Che Ghazali; Cindy Aulia Putri; Ashila Najwa; Virginia Frederika Salim (2026)
Non-Indexed Publication